Sensitive AC Hysteresigraph of Extended Driving Field Capability - Ercuta, Aurel (IEEE transactions on instrumentation and measurement, 2020)
An induction hysteresigraph using 50 Hz sine wave fields of 7 kOe maximum amplitude, generated by a solenoid-type multilayer coil, suitable for small amounts (down to tens of milligram) of magnetic materials is proposed. The changes in field and magnetization are detected by a field sensing coil and a compensated pick-up coil system , respectively, the as-induced signals being processed by two analog measuring channels ( channel H and channel M ), whose output signals reproduce the time evolution H(t) and M(t) of the two quantities. These signals are recorded via PC-assisted analog-to-digital conversion and then subjected to final numerical correction and calibration; apart from the demagnetizing field correction, the possible errors caused by the stray flux generated by the magnetized sample itself are also taken into account. In addition, instead of weak signals denoising via standard filtering or smoothing algorithms, reconstruction based on flexible combinations of transition-type fitting functions of time periodic argument is proposed. To prevent signal waveform distortions that can be caused by the frequency-dependent response of channel M , a thorough analysis is carried out in the time domain, by simulating the run of a 100 kHz bandwidth severe test signal, across the stages of this channel. This signal consists of sharp ac pulses, built as a digital replica of the electromotive force induced in a pick-up coil containing the sample, during its evolution along a steep-sided hysteresis loop; an original method, using a small number of parameters, is proposed to build the spectral expansion of the test signal.